(3ebGeGJ HOjY GdReGfs - (3HOjY GdReGf, CMeO Hf MSjf Hf jMji, J(B398(3g`s ((3eMeO QMeI Gddgs)
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd fYeGFgagPG eeG CedGgG GdCSJGPCHh GdaVd HOjY GdReGf CMeO Hf GdMSjfj GdgePGfj QhGjJg Yf YjSi Hf gTGe ef ebGeGJ CHj GdaJM GdEScfOQjs
(3BNQgG (B:s
(3CMOK GdhUa aeG MGLJc abGd JZjH gPG GdhLg aVMc hhdGg UfGYg HGdWGFa aj GdeSJfSN eG UhQJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 115s
(3eYLe GdeDdajf(B: 1 / 130s
(3cTa GdXfhf(B: 2 / 1785s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs